2010
DOI: 10.1073/pnas.0907189107
|View full text |Cite
|
Sign up to set email alerts
|

Ancient DNA analyses exclude humans as the driving force behind late Pleistocene musk ox ( Ovibos moschatus ) population dynamics

Abstract: The causes of the late Pleistocene megafaunal extinctions are poorly understood. Different lines of evidence point to climate change, the arrival of humans, or a combination of these events as the trigger. Although many species went extinct, others, such as caribou and bison, survived to the present. The musk ox has an intermediate story: relatively abundant during the Pleistocene, it is now restricted to Greenland and the Arctic Archipelago. In this study, we use ancient DNA sequences, temporally unbiased sum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
161
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 208 publications
(169 citation statements)
references
References 50 publications
7
161
0
1
Order By: Relevance
“…(57) and muskoxen after 48 calendar ka B.P. (3,58). Although the precise timing of these population bottlenecks remain obscure (13), their occurrence during the mid-Wisconsin interstadials is consistent with the hypothesis by Guthrie (37).…”
Section: Discussionsupporting
confidence: 74%
“…(57) and muskoxen after 48 calendar ka B.P. (3,58). Although the precise timing of these population bottlenecks remain obscure (13), their occurrence during the mid-Wisconsin interstadials is consistent with the hypothesis by Guthrie (37).…”
Section: Discussionsupporting
confidence: 74%
“…From this they concluded environmental changes were more important than human impacts in causing extinctions. Similarly, Campos et al (2010) studied changes in the genetic diversity of muskoxen using bones from the Arctic. They found that major bottlenecks in genetic diversity, which they interpreted as reflecting bottlenecks in population size, were not correlated with the arrival dates of humans.…”
Section: Background: End-pleistocene Extinctions On the Mammoth Steppementioning
confidence: 99%
“…However, most studies have been limited to single regions and limited numbers of taxa (e.g., [14][15][16][17][18], and have been beset by uncertainties in the accurate dating of human and/or megafaunal remains [e.g., the Cuddie Springs site in Australia (19)(20)(21)]. We believe that the problem is better approached by considering several landmasses simultaneously and dealing explicitly with uncertainty.…”
mentioning
confidence: 99%